From Sound to Sound Space, Sound Environment, Soundscape, Sound Milieu or Ambiance …. Issue 1 (March 2018) - Solomos, Makis
Abstract : This article proposes approaching the phenomenon of sound as a fabric of relationships. Critiquing the notion of a sound object as it has become defined thanks to the fixity enabled by sound recording, it focuses on the characteristics of sound that converge towards a relational approach and suggests that there is an inextricable link between the vibrating object, the milieu in which the vibration spreads and the subject who listens. It is probably for this reason that current research — whether in music, sound art or other disciplines that centre on sound, from sound studies to environmental ecology — implicitly seeks to move beyond the concept of sound alone in favour of compounds that combine sound with other elements. While the notions of sound 'spaces' and sound 'environments' appear as the default options here, three other compounds in particular highlight, in their own way, the relational approach: 'soundscapes', 'sound milieus', and sound 'ambiances' and 'atmospheres'.